Dynamics of Compliance and Law Violation in Society : A Criminological and Sociological Study - Joko Suyono; Niken Arief Rahayuana; Evi Dwi Hastri (Res Judicata Law Review, 2024)
This study analyzes the factors influencing legal compliance and violations within society through criminological and sociological approaches. The primary objective of this research is to identify the reasons behind public compliance with laws and to reveal common motives for violations. This study employs a qualitative method, utilizing in-depth interviews and observations with selected respondents, as well as literature review to enrich the analysis. The findings indicate that legal compliance is often driven by social values, morality, and a sense of collective responsibility, while legal violations are largely caused by economic pressures, weak law enforcement, and public dissatisfaction with regulations deemed irrelevant. The implications of these findings suggest the need for a more adaptive and participatory approach in creating and enforcing regulations to effectively enhance public compliance.